Strategi Pengembangan Kawasan Wisata Berbasis Ekonomi Kreatif Di Kecamatan Teluk Segara Kota Bengkulu - Maulidina, Rachmani; Yunita, Mirna; Alfi, Muhammad (Jurnal Pendidikan Geografi Undiksha, 2025)
This study analyzes the supporting factors and obstacles in developing a creative economy based tourist area in the Gulf of Segara district and can then formulate a strategy for developing creative economy-based tourist areas in Bengkulu City Gulf district. The aim of this study is to be able to identify the supportive factors and barriers in the development of a tourism area based on creative economy as well as to formulate a new strategy in development of tourism areas based on the creative economy. The research method used in this research is the Qualitative Method. In this study, it can be stated that there are some supportive factors and obstacles in the development of creative economy-based tourist areas in the Gulf of Segara district of Bengkulu City, then through SWOT analysis on internal and external factors, it is possible to produce a good strategy against the development strategy of tourism district based on creative economy in Segara Gulf district, namely 4 strategy ; Strategy SO, ST, WO Strategy, and WT Strategy. Keywords: Strategy, development of tourist area, creative economy